THE INDONESIAN HALAL INDUSTRY IS REVIEWED FROM A MICROECONOMICS AND MACROECONOMICS PERSPECTIVE - Putri, Nurwahyu Hasanah; Peristiwo, Hadi (International Journal Mathla’ul Anwar of Halal Issues, 2024)
Halal industry is an effort to process raw goods into finished or semi-finished goods using facilities/equipment whose licenses are in accordance with Islamic law. The large number of Muslim population in Indonesia has a positive impact on the development of the halal industry in Indonesia. In its development, the halal industry is divided into several sectors including halal food, halal fashion, halal pharmacy, halal tourism, halal finance, etc. This study was conducted to review Indonesian halal industry from a microeconomics and macroeconomics perspective. This research uses literature study obtained from various books and relevant journals. The results of this study are in the form of data on Indonesian state revenues and expenditures generated from the halal industry and their effects on the Indonesian economy.